Start reading: finn's Fortune: finn and the king of cork - Gowar, Mick; Tim Archbold (Wayland Sydney, 2009)
Finn and Jim the Carter are off to Cork to deliver some goods to the Mayor. The Mayor wants to win the reward offered to anyone who can make the King laugh, but the joke noses, whoopee cushions and tickle sticks don't work. What can they do to make the King laugh?